The Impacts Of Climate Change On The Health And Well-being Of The Peoples Of Whitefish River First Nation, Ontario - Sritharan, Mahisha (2017)
Indigenous communities in Canada are some of the most vulnerable to the impacts of climate change. Research has tended to focus more on the Arctic region in Canada and more recently, a need to understand how climate change is impacting First Nations communities in the Great Lakes region has emerged. Whitefish River First Nation is an Anishinaabe community located on the northern shores of Georgian Bay in Lake Huron in the Great Lakes Ecosystem of Ontario. This qualitative research study, by working with the Whitefish River First Nation aimed to address how a First Nations community’s health and well-being is being impacted by climate change. Indigenous research methodologies and environmental justice concepts were used to frame this research study. Through focus groups with community members and Elders and key informant interviews, information and knowledge from participants of Whitefish River First Nation was gathered and analyzed. Impacts to the community’s health and well-being as a result of climate change and other environmental stressors was shared. Based on the discussions and adaptation strategies that emerged from the community, this paper outlines recommendations for how to move forward and address the impacts of climate change on First Nations communities in the Great Lakes region.